Costless and costly prosociality: correspondence among personality traits, economic preferences, and real world prosociality - Ferguson, Eamonn; Zhao, Kun; O'Carroll, Ronan; Smillie, Luke (SAGE, 2018)
Prosociality can either be costly (e.g., donating to charity) or costless (e.g. posthumous organ donation). Whereas links between personality and costly prosociality and have been explored, links with costless prosociality and personality are at present unknown. We address this in two studies. Study 1 (N = 200) confirms the distinction between costless and costly prosociality based on willingness to engage with health and non-health prosociality. Study 2, using data from 4 samples (student and community; N = 733) shows that across incentivized and hypothetical economic games to assess costless (generosity game; GG) and costly (dictator game; DG) prosociality, that organ donor behavior was linked to greater allocations in the GG and charity/volunteering behavior in the DG. Costless and costly prosocialities are associated with different personality traits (e.g., costly with politeness and compassion, and costless with intellect). Implications for cooperative phenotypes and recruiting organ donors are discussed.